Human Papilloma Virus Prevalence and Types among Iranian Women Attending Regular Gynecological visits - Shafaghi, Behrouz; Jarollahi, Ali; Yousefzadeh, Bahman; Ameri, Ahmad; Moghadam, Shiva; Mostafavi, Mostafa (Reports of Radiotherapy and Oncology, 2024)
Introduction: Human papilloma virus prevalence data is scarce in Iran. This study was performed to evaluate type-specific human papilloma virus prevalence and to compare it with Pap smear results among Iranian women attending regular gynecological visits. Patients and Methods: A total of 851 women aged 18-65 years, attending regular gynecological visits were retrospectively evaluated. Human papilloma virus detection and genotyping was performed using polymerase chain reaction technique. Cytological evaluation was performed by Papanicolaou method and the association between cytological results and human papilloma virus profile was analyzed. Results: Nineteen different types of human papilloma virus were detected in 265 of 851 patients (31.1%). Overall infection as well as infection with high risk human papilloma virus types; were highest in women aged 18-25 years and decreased with age. Type-specific prevalence of human papilloma virus -16 and 18 was 7.3% and 2.8% respectively. There was also an upward trend in the prevalence of high risk human papilloma virus infection as the abnormality in cytology increased. The prevalence of human papilloma virus related events was 29.1% among virus positive patients and declined from low grade squamous intraepithelial lesion (18.2%) to high grade squamous intraepithelial lesion (3.9%).